Diet Quality and Micronutrient Intake among Long-Term Weight Loss Maintainers - Pascual, Rebecca W. (Nutrients, 2019)
Inadequate vitamin and mineral intake is documented among individuals with obesity, but is unknown among long-term weight loss maintainers (WLM). This study examined dietary quality and micronutrient adequacy among WLMs in a commercial weight management program. Participants were 1207 WLM in Weight Watchers (WW) who had maintained a 9.1 kg or greater weight loss (29.7 kg on average) for 3.4 years and had a body mass index (BMI) of 28.3 kg/m(2). A control group of weight stable adults with obesity (controls; N = 102) had a BMI of 41.1 kg/m(2). Measures included the Diet History Questionnaire-II, Healthy Eating Index-2015 (HEI), and Dietary References Intakes. WLM versus controls had a 10.1 point higher HEI score (70.2 (69.7–70.7) vs. 60.1 (58.4–61.8); p = 0.0001) and greater odds of meeting recommendations for copper (OR = 5.8 (2.6–13.1)), magnesium (OR = 2.9 (1.8–4.7)), potassium (OR = 4.7 (1.4–16.5)), vitamin A (OR = 2.8 (1.7–4.8)), vitamin B6 (OR = 2.9 (1.6–5.2)), and vitamin C (OR = 5.0 (2.8–8.8)). WLM, compared to controls, also reported higher percentages of calories from carbohydrates (50.3% (49.7–50.8) vs. 46.7% (44.8–48.7); p = 0.0001) and protein (18.2% (18.0–18.5) vs. 15.9% (15.1–16.6); p = 0.0001) and lower calories from fat (32.3% (31.9–32.8) vs. 37.4% (35.8–38.9); p = 0.0001). Long-term weight loss maintenance in a widely used commercial program was associated with a healthier diet pattern, including consuming foods with higher micronutrient density.